Brush Deformation Effects on Poly Vinyl Acetal Brush Scrubbing. (1st January 2018) - Ito, M.; Sanada, T.; Fukunaga, A.; Hiyama, H.
Abstract : PVA brush scrubbing techniques are widely used in cleaning processes for semiconductor device manufacturing. These cleaning processes are typically monitored by measuring the forces or torques generated during PVA brush scrubbing. In this paper, we discuss whether these measured parameters reflect the real contact conditions during scrubbing. We measured the shear forces generated by brush sliding. The shear forces were strongly correlated with brush deformation. In addition, brush rotation greatly suppressed brush deformation and shear force. This result indicates that a portion of the shear force was generated by brush deformation and not contact conditions. We also measured the torque generated by the PVA brush rotation on a surface. We concluded that these types of measurements, which reduced brush deformations, were suitable for evaluating contact conditions.